Bacterial cellulose: Molecular regulation of biosynthesis, supramolecular assembly, and tailored structural and functional properties. (August 2022) - Manan, Sehrish; Ullah, Muhammad Wajid; Ul-Islam, Mazhar; Shi, Zhijun; Gauthier, Mario; Yang, Guang
Graphical abstract: A schematic illustration of the molecular regulation of intracellular synthesis, extracellular transport, and in vitro assembly of cellulose fibrils into highly-ordered supramolecular structures for the development of functionalized biomaterials for specialized applications. Abstract: Among the different types of nanocellulose being investigated, bacterial cellulose (BC) or bacterial nanocellulose (BNC) is receiving tremendous attention due to its purity and superior features. Either alone or in the form of composites, BC finds diverse applications in different fields. However, the low yield and productivity of BC by microbial cells and the high cost of the bioreactors and medium components, perhaps due to limited knowledge of its biosynthesis mechanism and extracellular transport in microbial cells, are major constraints to the industrial-scale production and commercial applications of BC and BC-based products. Molecular studies revealed the involvement of specific operons ( bcsABCD ) in the biosynthesis, extracellular transport, and in vitro supramolecular assembly of cellulose fibrils. The yield and productivity, as well as the innate structural and functional properties of BC, can be modulated through genetic and metabolic modeling, which requires comprehensive genetic knowledge obtained through genome sequencing of the BC-producing bacterial strains. Thanks to the latest developments in genetic engineering, various bacterial strains have been engineered via overexpression or the knockdown of target genes, not only to enhance the BC yield and productivity but also to improve its structural features such as the density, porosity, and mechanical strength of the fibers, as well as to achieve the in situ functionalization of BC for specific applications. This review describes the molecular aspects of the biosynthesis, regulation, and organization of cellulose nanofibrils into highly ordered structures by BC-producing bacterial cells. It further discusses the control of structural features of BC at the molecular level, both to improve its innate features and impart additional functional properties. Overall, this review aims to provide a platform for molecular biologists and material engineers to improve BC production and develop strategies for the in vivo development of BC-based hybrid materials with improved and novel features for various bio-oriented applications.